Factor Analysis of Increasing Customer Loyalty in The Automotive Industry - Annisa Tri Wahyuni; Triwulandari SD; Rina Fitriana (CV. Syntax Corporation Indonesia, 2023)
This study aims to analyze the factors that influence loyalty in the automotive industry. The population of this study are car owners who live in Jabotabek . Using two types of questionnaires, namely the screening questionnaire and the main questionnaire consisting of 27 indicators. Probability sampling was used in determining the sample so that 135 samples were obtained which were dominated by Toyota and Honda brand users with the MVP segment. Factor analysis was carried out using the SEM (structural equation model) method with Smart PLS software and tested the validity, Cronbach's Alpha reliability test and goodness of fit to test the structural model. The results showed that among the 3 variables, namely brand image, product and staff, only brand image proved to have a positive and significant effect on loyalty (50.1%), while the product and staff variables had no significant effect. With the results of this study, it is hoped that ATPM can maintain the loyalty of their customers by continuing to improve their brand image by paying attention to 7 indicators, namely reliable, advanced, challenging, creative, sophisticated, luxury and sustainable.